Faktor-Faktor yang Mempengaruhi Kemiskinan di Propinsi Sumatera Barat - Yenni Del Rosa (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research aims to analyze how much influences the economic growth, inflation and unemployment poverty the province West Sumatra.  Economic growth, inflation and employment panel data were collected from thr Central Statistics Agency in 2014 – 2018 with saturated sampling technique. Multiple regression equation obtained from this study Y = 179,02 -  0.087 X1 – 0,033X2 + 0,006X3 +  e with a coefficient of determination of 0.949 and a correlation coefficient of 0.866 and adjusted R square 0,549 . After testing the hypothesis turns out the hypothesis is accepted where economic growth and inflation significant negative effect on poverty  and unemployment has no significant positive effect on poverty.